Descartes' Meditations on first philosophy : an Edinburgh philosophical guide - Brandhorst, Kurt (Edinburgh philosophical guides series., 2010)
Descartes' Meditations is one of the first texts that a philosophy student will study, and one that many come back to time and again. Rather than simply telling the reader what to think, Meditations invites us to take a philosophical journey. This book prepares readers for that journey, helping them to engage with each of the meditations and suggesting ways through the more difficult passages. This guide also offers students a fresh approach by bringing to life the path of self-discovery encapsulated in the work, while maintaining the emphasis on metaphysics. By focusing on what the text itsel.